Optimism for Recovery in Rehabilitation Residents at IPWL (Recipient Institutions Required to Report) Sriwijaya, South Sumatra - Utari Tinova, Diah; Aprilian Nugraha, Ester; Engla Romasia, Try (International Journal of Social Science, Education, Communication and Economics, 2024)
This research discusses optimism for recovery in rehabilitation residents at IPWL (Compulsory Reporting Recipient Institution) Sriwijaya, South Sumatra. This research uses a qualitative method with a descriptive design. The subject selection technique is using purposive sampling with criteria,Male, 16 - 23 years old, Muslim, Older Status and Older Phase. Data collection methods use interview methods, as well as observation and documentation. The results of this research generally showed that the four subjectsThe image of Recovery Optimism is to change into a better person, and not want to be involved with drugs again. Factors that influence optimism are family factors such as providing motivation to residents, personal factors, namely changes in the subject that they have made away from drugs and maintaining recovery.